Unemployment as a chronic stressor: A systematic review of cortisol studies. Issue 3 (4th March 2017) - Sumner, Rachel C.; Gallagher, Stephen
Abstract : Objective: Unemployment is a type of chronic stressor that impacts human health. The reasons for how the stress of unemployment affect health is still a matter of discussion. One of the pathways from chronic stress to ill health is mediated by cortisol, and so we set out to compile extant data on how its secretion is affected by unemployment. Design: A systematic literature search was conducted to establish the cortisol dysregulatory effects of this stressor. Main outcome measures: Only studies that specifically examined the effects of unemployment on cortisol excretion, and were written in English were included. Results: Ten reports were obtained and synthesised to determine the severity and complexity of the effect of unemployment on cortisol secretion. The resulting combined evidence is mixed in terms of degree or dynamic of relationship. Conclusions: The differences between the cumulate findings of the studies can be understood in the context of the lack of both standardised methodology and an absence of consensus on unemployment definition. We propose existing methodologies may be strengthened by acknowledging and accounting for the individual characteristics that may be relevant to the stress experience of unemployment.